THE LANGUAGE STYLE ANALYSIS OF FURY MOVIE BY DAVID AYER (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims: (1) To find out how many different language styles are used in Martin Joos’s Fury film. (2) To find out which is the dominant type of language style in Fury movie. Because the data in this study is a movie dialogue transcribed into textual form, the researcher uses a qualitative method to collect data by watching the movie, identifying the conversation that contains language style on communication, classifying based on the types of language style found in the movie, and determining the dominant type of language style. This research came to two conclusion. The first was four out of five different types of language styles. The second point was that, of the four styles, casual style was the most prevalent, while frozen style was absent from the film “Fury”. The formal style has 29 data points, the consultative style has 97, the casual style has 102, and the intimate style has 13 data points. The use of language style reveals that the most common type of language style is a casual style, which contains 102 data.